Pengembangan Media Diorama Berbasis Lingkungan Sosial untuk Meningkatkan Hasil Belajar Siswa Kelas IV dalam Pembelajaran PPKn - Fazalika Syahputra; Puspa Djuwita; Bambang Parmadi (Jurnal Kajian Pendidikan Dasar, 2024)
The purpose of this study was to develop, describe the level of feasibility, determine user responses and determine the effectiveness of social environment-based diorama media to improve student learning outcomes. The type of research used is research and development (Research and development). The research model in the development of 4 dimensions. The types of data used are quantitative and qualitative data with instruments: interviews, needs analysis questionnaires, questions, expert validation sheets and user response questionnaires. Based on the results of the study it was concluded that the teaching materials developed were suitable for use as teaching materials in learning Pancasila and Citizenship Education (PPKN) class IV let's love the environment. Expert validation was carried out for aspects of design feasibility, materials and media. Percentage of validation results of design aspects (83%), materials (71%) and media (90%). Based on the results of the questionnaire, student responses to PPKN teaching materials with the material let's love the environment in the very good category. Environment-based diorama teaching media to improve student learning outcomes in class IV SD Negeri 27 Lubuklinggau based on effect size (1.507) with a very effective category for improving student learning outcomes.